2017
DOI: 10.1111/add.13693
|View full text |Cite
|
Sign up to set email alerts
|

Cannabis use during treatment for alcohol use disorders predicts alcohol treatment outcomes

Abstract: Aims (1) Compare post-treatment alcohol use between those who use cannabis and those who abstain during treatment for alcohol use disorders (AUD). (2) Examine potential cannabis use thresholds by comparing post-treatment alcohol use between four frequency groups of cannabis users relative to abstainers. Design Secondary analyses of the COMBINE Study, a randomized control trial of AUD treatments. The current study compares longitudinal drinking data between those who used cannabis vs. those who abstained duri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
65
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 61 publications
(72 citation statements)
references
References 47 publications
4
65
3
Order By: Relevance
“…The lack of significant associations between cannabis use and alcohol-related problems across most domains is interesting and consistent with previous findings of a lack of association between heavy drinking and cannabis frequency in the COMBINE sample (Subbaraman et al, 2017). Taken together, the results from the current and previous studies signal that more work is needed to understand whether there are safe levels of cannabis use for individuals in AUD treatment.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…The lack of significant associations between cannabis use and alcohol-related problems across most domains is interesting and consistent with previous findings of a lack of association between heavy drinking and cannabis frequency in the COMBINE sample (Subbaraman et al, 2017). Taken together, the results from the current and previous studies signal that more work is needed to understand whether there are safe levels of cannabis use for individuals in AUD treatment.…”
Section: Discussionsupporting
confidence: 90%
“…The primary exposure was cannabis use during treatment, defined by quartiles among users (n = 206) with cannabis abstainers as the referent (n = 999). Following previously published analyses that showed differential effects of cannabis according to frequency of use (Subbaraman et al, 2017), cannabis users were grouped into quartiles based on the distribution of the percentage of days of cannabis use during the 16week treatment period: Quartile 1 (Q1; approximately 1–4% of days, or less than 1x/month), Quartile 2 (Q2; approximately 5–8% of days, or 1–2x/month), Quartile 3 (Q3; approximately 9 – 39% of days, or 4–8x/month), and Quartile 4 (Q4; approximately 40–100% of days, or 12x/month or more).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Given the high prevalence of marijuana use among men in BIPs identified in the present study, and our preliminary finding that marijuana and alcohol use and problems interact to predict sexual IPV, it is plausible that marijuana use could negatively impact BIP outcomes. Indeed, individuals who are in alcohol treatment have poorer outcomes when they are using marijuana during treatment relative to individuals who do not use marijuana during treatment (Subbaraman, Metrik, Patterson, & Swift, 2017). Therefore, BIPs should consider targeting marijuana use in their programs in order to determine whether marijuana use treatment impacts BIP outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, literature examining the impact of marijuana use on the treatment of other substances is mixed. With the exception of a few studies that do not show marijuana use to negatively influence alcohol or smoking cessation outcomes (Magill et al, 2009; Metrik et al, 2011), many studies have demonstrated that using marijuana before or during alcohol treatment is associated with higher levels of drinking at follow-up (Alessi et al, 2011; Mojarrad et al, 2014; Subbaraman et al, 2016). For example, among alcohol dependent individuals, those who used marijuana during alcohol treatment reported fewer days abstinent from alcohol one year following treatment than those who did not use marijuana (Subbaraman et al, 2016).…”
Section: Introductionmentioning
confidence: 99%